Adsorption of 3d transition-metal atom on Stone-Wales defected arsenene: A theoretical study. (June 2019) - Zhou, Qingxiao; Ju, Weiwei; Su, Xiangying; Yong, Yongliang
Abstract: Using first-principles calculations, we investigated the electronic and magnetic properties of arsenene functionalized by Stone-Wales (SW) defect and 3d transition-metal (TM) atoms (from Sc to Zn). The producing of the SW-defect increased the band gap, while the SW-defected arsenene still exhibited nonmagnetic. Furthermore, the large adsorption energies and charge transfer indicated chemisorptions of TM-adatoms except for the Zn atom. The electronic structures showed that strong hybridizations existed between the TM-d orbital and As-p orbital. Interestingly, the dilute magnetism of SW-defected arsenene substrate can be modified by the adsorption of TM-atoms. Moreover, the magnetic properties were mainly contributed by the TM-adatoms and the As atoms around the SW-defect. Present results could provide useful information to develop new arsenene-based electronic and spintronic devices. Highlights: The presence of Stone-Wales (SW) defect increase the band gap of arsenene. The SW-defected arsenene was n-doped by the adsorption of TM-atoms. The dilute magnetism of SW-defected arsenene can be modified by TM-adatoms.